Enhancement of CO2 conversion in microwave plasmas using a nozzle in the effluent. (March 2022) - Hecimovic, Ante; D'Isa, Federico A.; Carbone, Emile; Fantz, Ursel
Highlights: Improvement of CO2 conversion in microwave plasma towards and at atmospheric pressure is obtained by using a nozzle in the effluent. Improving wall-plug efficiency–increase of CO2 conversion at atm. pressure. Achieving supersonic expansion requires nozzle diameters of 2.5 mm. Abstract: Plasma conversion is an alternative approach to the electrochemical and photochemical technologies searching for most efficient way to convert CO2 into carbon monoxide (CO). The CO2 plasma conversion investigated in recent years demonstrated conversion and energy efficiencies up to 50%. Commonly, these values are obtained at pressures lower than atmospheric pressure at about 100 mbar. In this work we present an investigation of the CO2 conversion and the energy efficiency in a microwave plasma torch equipped with a nozzle of different diameters installed downstream of the plasma at varying distances to the microwave discharge, in the pressure range 100–900 mbar. The results obtained using the nozzle demonstrate an enhancement of conversion and energy efficiency, particularly at pressures close to atmospheric pressure and for lower CO2 flows (SEI above 2 eV/molecule), bringing the values of conversion and energy efficiency close to those obtained at lower pressures. It is assumed that the fast cooling of the hot plasma gas with surrounding colder gas leads to reduction of CO recombination into CO2 thus preserving the maximum conversion obtained. With a 2.5 mm nozzle at sub-atmospheric pressures, conditions with large pressure difference in the resonator and in the effluent are observed, which is accompanied by an additional increase in conversion. A likely reason for this is reduction of the recombination rates due to lowering of the pressure in the effluent and possible temperature reduction resulting from the supersonic expansion. Using the nozzle it is possible to significantly increase the performance of the plasma torch at 900 mbar, both in conversion and energy efficiency towards values achieved at 200 mbar, which is an important step towards industrial applicability of this technology.